Computational program to estimative of herbicide droplet uniformity applied by aerial spraying - Pessoa, Maria Conceição Peres Young; Chaim, Aldemir (Pesquisa Agropecuaria Brasileira, 1999)
The main objective of this work was to present an algorithm of the computational program based on a numeric method to estimate losses of herbicides caused by aerial spraying. This method has as input, the frequency of droplets sizes collected on water sensitive paper, observed on the Porton graticule coupled to the microscope. With this values the accumulated distribution of the mean diameter is computed for droplets size and for droplets volume, both formed by the spraying nozzle, following already known methodology. Data obtained for this two distribution curves make possible to use a numeric method of the linear interpolation in order to obtain the volume median diameter and the numeric median diameter. These two values are fundamental to the determination of the droplets uniformity. This method was implemented on computer language to enable users to compare observed values against estimated by interpolation techniques. An example of the program is presented for an hydro sensitive paper capture on the sampling carried out in Pelotas, RS, Brazil.